An empirical study on the returns to scale of supply structure in China's economic growth: 1993–2015. Issue 2 (2nd December 2019) - Ren, Baoping; Jie, Wei
Abstract : Purpose: Constant or decreasing returns and increasing returns to scale are two kinds of mechanism in economic growth. The goal of supply-side structural reform is to promote the establishment of the mechanism with increasing returns to scale. The paper aims to discuss this issue. Design/methodology/approach: This paper argues that the overall economic structure of the developing economy has been divided into the sector of constant or decreasing returns to scale and the sector of increasing returns to scale due to the dual economic structure. Among them, the supply-side structural reform is mainly to reduce the sector of decreasing returns to scale and increase the sector of increasing returns to scale. Based on the hypothesis of such two-sector economic structure in the supply side of developing economies and on the industrial data, this paper empirically tests the returns to scale of China's supply structure. The result suggests that so far the sector of constant or decreasing returns to scale dominates the supply structure of China's economic growth, which results in the state of decreasing returns to scale in China's overall economy. Findings: Therefore, to realize the long-term sustained growth and transformation of the development pattern of China's economy, the authors must carry out the supply-side structural reform, vigorously develop the modern industrial sectors characterized by modern knowledge and technology, and promote the development of an innovation-driven economy. Originality/value: Besides, the authors must accelerate the transformation from traditional industrial sectors to modern industrial sectors, actively promote China's industrial structure toward rationalization and high gradation, as well as build a modern industrial system so as to facilitate the formation of the mechanism of increasing returns to scale and accelerate the transformation of the driving force of China's economic growth.